A Brief Analysis on Constructivism Theories and Intermediate Chinese Conversation Teaching - Temmy, Temmy (Bina Nusantara University, 2013)
Constructivism theories believe that learning process should be conducted under a specific condition, which is social and cultural background of the target language. Learner’s language ability is built through communication and activities that helps to shape meaningful construction. This theory has a very high impact on teaching conversation. This article discusses the Constructivism theory, its relation on learner’s word production, psychological mechanism and teaching intermediate conversation’s characteristics, as well as the feasibility and applicability of Constructivism theory in the process on teaching intermediate conversation.